2004
DOI: 10.4314/sajas.v33i3.3774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress produced by adrenocorticotropin (ACTH) on lipid peroxidation and some antioxidants in vitamin C treated and nontreated chickens

Abstract: The aim of this study was to examine the effects of vitamin C on malonaldehyde (MDA) and glutathione (GSH) concentrations, and superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activity in chickens stressed by adrenocorticotropin (ACTH). Sixty Leghorn chickens (20 weeks old) were randomly allotted to a control and a vitamin C treated group. An isotonic sodium chloride solution was administrated intramuscularly for a period of five days to the control group at a dose of 2.5 mL per chicken per day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Belge et al . () also reported that AA exerts its antioxidative effect by removing singlet oxygen, hydroperoxyl, superoxide, lipid peroxyl and lipid free radicals, and thus decreases MDA concentration in animals subjected to stress. The significant increase in MDA activity recorded in groups B and C are in agreement with that of Nazifi et al .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Belge et al . () also reported that AA exerts its antioxidative effect by removing singlet oxygen, hydroperoxyl, superoxide, lipid peroxyl and lipid free radicals, and thus decreases MDA concentration in animals subjected to stress. The significant increase in MDA activity recorded in groups B and C are in agreement with that of Nazifi et al .…”
Section: Discussionmentioning
confidence: 87%
“…the administration of AA even after transport reduced the effect of stress and enhance regaining of lost weight. Lipid peroxidation is the oxidative deterioration of polyunsaturated lipids, which leads to the production of a degraded product, called MDA (Belge et al 2003). The increase in MDA activity in group A following transportation was not significant as compared to groups B and C which recorded significant MDA activity following transportation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Avellini et al (1995) noted that ROS are known to play a vital role in tissue damage and has adverse effects on erythrocyte. It is known fact ROS are generated in animals subjected to stress (Halliwell, 1996) leading to lipid peroxidation a complex process which leads to membrane damage and cell death (Belge et al, 2003). Lipid peroxidation is the oxidative deterioration of polyunsaturated lipids, leading to the production of a degraded product called malondialdehyde (Belge et al, 2003) in which its concentration is a biomarker for ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known fact ROS are generated in animals subjected to stress (Halliwell, 1996) leading to lipid peroxidation a complex process which leads to membrane damage and cell death (Belge et al, 2003). Lipid peroxidation is the oxidative deterioration of polyunsaturated lipids, leading to the production of a degraded product called malondialdehyde (Belge et al, 2003) in which its concentration is a biomarker for ROS generation. The result of the present study showed that MDA concentration as well as the degree of haemolysis increases as the journey progresses especially in group 3 (control) which was not administered any antioxidant.…”
Section: Discussionmentioning
confidence: 99%